If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-5)=4x-(10x+2x)
We move all terms to the left:
2(x-5)-(4x-(10x+2x))=0
We add all the numbers together, and all the variables
2(x-5)-(4x-(+12x))=0
We multiply parentheses
2x-(4x-(+12x))-10=0
We calculate terms in parentheses: -(4x-(+12x)), so:We get rid of parentheses
4x-(+12x)
We get rid of parentheses
4x-12x
We add all the numbers together, and all the variables
-8x
Back to the equation:
-(-8x)
2x+8x-10=0
We add all the numbers together, and all the variables
10x-10=0
We move all terms containing x to the left, all other terms to the right
10x=10
x=10/10
x=1
| Y=-x²+2x-2 | | 44=k/10+37 | | -2x+-8=2x | | Y=a(0.8) | | 23/c= | | -7=5r=2r | | -56=8(a-6) | | 23c= | | 70=20-10x | | 1/2x+1/3x+5=90 | | 4v+3=6v-5 | | 49-13-7n=-6-9(n+3) | | X^2-14=2x-4 | | Y=a(1.1) | | 4=1+p/3 | | 0.3x−0.2=4.3 | | 3(5a+10)+10=6a-(a+10) | | s+10/7=3 | | 80=10(z+1) | | 4(2y+10)=2(y-13) | | x–57=135 | | 10=-10d-20 | | 97-18=54x | | 12=3j+3 | | (5x)×(3x)=100 | | .25x=1000 | | .26x=1000 | | 5+3x=–1+4x | | 1/9x+9=17 | | 7x+5x-6x=8-5x | | 99−11t= −88−88 | | 122=1/2(96+x) |